Hippocampus-Anterior Hypothalamic Circuit Modulates Stress-Induced Endocrine and Behavioral Response - Bang, Jee Yoon; Zhao, Julie; Rahman, Mouly; St-Cyr, Sophie; McGowan, Patrick O.; Kim, Jun Chul (Frontiers in Neural Circuits, 2022)
Hippocampal input to the hypothalamus is known to be critically involved in mediating the negative feedback inhibition of stress response. However, the underlying neural circuitry has not been fully elucidated. Using a combination of rabies tracing, pathway-specific optogenetic inhibition, and cell-type specific synaptic silencing, the present study examined the role of hippocampal input to the hypothalamus in modulating neuroendocrine and behavioural responses to stress in mice. Trans synaptic rabies tracing revealed that the ventral hippocampus (vHPC) is monosynaptically connected to inhibitory cells in the anterior hypothalamic nucleus (AHN-GABA cells). Optogenetic inhibition of the vHPC→AHN pathway during a restraint stress resulted in a prolonged and exaggerated release of corticosterone, accompanied by an increase in stress-induced anxiety behaviours. Consistently, tetanus toxin-mediated synaptic inhibition in AHN-GABA cells produced a remarkably similar effect on corticosterone release profile, corroborating the role of HPC→AHN pathway in mediating the hippocampal control of stress responses. Lastly, we found that chronic inhibition of AHN-GABA cells leads to cognitive impairments in both object and social recognition memory. Together, our data present a novel hypothalamic circuit for the modulation of adaptive stress responses, the dysfunction of which has been implicated in various affective disorders.